Mīmāṃsānayavivekaḥ - Bhavanāthamiśra ca. ca. 1050-1150
Classical commentary, with supercommentaries, on Jaiminis Mīmāṃsāsūtra, basic work of the Mīmāṃsā school in Hindu philosophy, presenting the tradition of Prabhākara Miśra